Severe Neonatal COVID Pneumonia With Cytokine Storm. Issue 4 (December 2022) - Singh, Vineet Kumar; Tripathi, Shalini; Kumar, Mala
COVID infection is not as common in children as in adults. In the first wave, symptomatic SARS-CoV-2 infection was less common with mild symptoms in children and neonates. But in the second wave, more children and neonates were affected with severe manifestations. COVID infection in neonates is mostly asymptomatic and published data from various neonatal units of India shows that most COVID positive newborns have good prognosis; poor outcomes are due to perinatal complications and rarely due to COVID. 1 However, in the second wave, newborns too were affected. We are presenting the case of a preterm neonate who developed severe COVID pneumonia on day 10 of life with cytokine storm and succumbed to death.